Characterization of diamond-like carbon thin film synthesized by RF atmospheric pressure plasma Ar/CH4 jet. (January 2016) - Sohbatzadeh, Farshad; Safari, Reza; Etaati, G.Reza; Asadi, Eskandar; Mirzanejhad, Saeed; Hosseinnejad, Mohammad Taghi; Samadi, Omid; Bagheri, Hanieh
Abstract: The growth of diamond like carbon (DLC) on a Pyrex glass was investigated by a radio frequency (RF) atmospheric pressure plasma jet (APPJ). The plasma jet with capacitive configuration ran by a radio frequency power supply at 13.56 MHz. Alumina ceramic was used as dielectric barrier. Ar and CH4 were used in atmospheric pressure as carrier and precursor gases, respectively. Diamond like carbon thin films were deposited on Pyrex glass at substrate temperature and applied power of 130 °C and 250 Watts, respectively. Performing field emission scanning electron microscope (FE-SEM) and laser Raman spectroscopy analysis resulted in deposition rate and the ID /IG ratio of 21.31 nm/min and 0.47, respectively. The ID /IG ratio indicated that the coating possesses relative high sp3 content The optical emission spectroscopy (OES) diagnostic was applied to diagnose plasma jet species. Estimating electron temperature and density of the RF-APPJ resulted in 1.36 eV and 2.75 × 10 14 cm −3 at the jet exit, respectively. Highlights: The growth of DLC using atmospheric pressure plasma jet. Investigation of structural and morphological properties of DLC deposited thin film. Estimation of plasma jet electron temperature and density using OES analysis.